Incidental lexical mining in task repetition: The role of input, input repetition and individual differences. (December 2021) - Duong, P.T.; Montero Perez, M.; Nguyen, L.Q.; Desmet, P.; Peters, E.
Abstract: The present study examined the effects of input, input repetition and individual differences (i.e., prior vocabulary knowledge and working memory) on L2 learners' incidental lexical mining in an immediate and a repeat oral task. Ninety participants were allocated to three groups: input (n = 32), input repetition (n = 29), and no input (n = 29). The input group was exposed to input before performing an immediate oral task, whereas the input repetition group was exposed to input before and after performing the immediate oral task. The no input group only performed the oral task without input exposure. Three groups repeated the same oral task after two days. Lexical mining was measured as the number of words and formulaic sequences shared between the oral tasks and the input text. The findings showed that the participants could mine both single words and formulaic sequences in the immediate and the repeat oral task. Yet, while the number of shared words in the repeat oral task was the same as in the immediate oral task, the number of shared formulaic sequences was lower. There was no effect of input repetition on lexical mining in the repeat oral task. Finally, only prior vocabulary knowledge was positively correlated to lexical mining.